Converting colonialism: visions and realities in mission history, 1706 - 1914 - Robert, Dana Lee (Studies in the history of Christian missions, 2008)
Mission reports from South India and their impact on the western mind : the tranquebar mission of the eighteenth century / Daniel Jeyaraj -- The Christian vision and secular imperialism : missionaries, geography, and the approach to East Africa, c. 1844-1890 / Roy Bridges -- Evangelicalism, islam, and millennial expectation in the nineteenth century / Andrew Porter -- The Church Missionary Society and the indigenous church in the second half of the nineteenth century : the defense and destruction of the Venn ideals / C. Peter Williams -- Evangelical missions and racial 'equalization' in South Africa, 1890-1914 / Richard Elphick -- The 'Christian home' as a cornerstone of Anglo-American missionary thought and practice / Dana L. Robert -- From Krishna pal to Lal Behari Dey: Indian builders of the church in Bengal, 1800-1894 / Eleanor Jackson -- Indigenous agency, religious protectorates, and Chinese interests : the expansion of Christianity in nineteenth-century China / R.G. Tiedemann -- A new Christian politics : the mission-educated elite in West African politics / J.F.A. Ajayi